Students’ Responses Towards Quizizz as the Assessment Learning Tool for 10th Grade Students of SMAN 5 Semarang - Gigih Rizqi Adhi; Wiyaka Wiyaka; Siti Lestari (Verba: Journal of Applied Linguistics, 2023)
Quizizz is presently the most popular online educational application for learning media and assessment tools. Teachers can assess students' learning abilities quickly, easily, and systematically while using it. It has attractive audio-visual features, humorous memes, stunning themes, and comprehensive assessment analysis for educators. Due to these benefits, many educators use Quizizz for educational purposes. Consequently, the purpose of this study is to investigate how students react to Quizizz as an assessment instrument for English language learning and investigate the effectiveness of Quizizz as a fun assessment tool for students, as well as the difficulties encountered by students when using the Quizizz application to take tests. This study found that the average response rate of 82.34% based on questionnaires and interviews with students, indicating that Quizizz has a positive impact on students. This response shows that students are enthusiastic and engaged in learning, thus enhancing their learning outcomes.